GROWTH RESPONSE AND YIELD OF ONION (Allium ascalonicum L) AGAINST CHICKEN MANURE FERTILIZER AND DIFFERENT OF CROPPING DISTANCE APPLICATION - Andre Wahyu Pratama; Ansoruddin Ansoruddin; Sri Susanti Ningsih (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted in Dusun Benteng Jaya Village, Sei Balai Subdistrict, Batu Bara District, Province North Sumatera with altitude of place 5 m asl, flat topography and climate type C. The research was conducted in May 2017 to 2017. This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor is the dosage of chicken manure (A) fertilizer with 4 levels: A0 0 kg / plot, A1 = 0.5 kg / plot, A2 = 1.0 kg / plot and A3 = 1.5 kg / plot. The second factor was treatment of crop distance (J), with 3 levels ie J0 = 20 cm x 20 cm (25 plants per plot), J1 = 20 cm x 25 cm (20 plants per plot), and J3 = 20 cm x 50 cm (10 plants per plot). The results of the treatment of chicken manure have a significant effect on the growth and production of onion, with the best dose at 1.5 kg / plot (A3)treatment. Different plant distance treatment significantly affected on growth and production of onion, with the best cropping distance 20 cm x 50 cm (J3). The interaction between chicken manure application and different cropping distance treatment on growth and production of onion showed no significant effect on all parameters observed.